Physical Activity and Cognition: Inseparable in the Classroom - Doherty, Anya; Forés Miravalles, Anna (Frontiers in Education, 2019)
Traditional education has tended to compartmentalize abstract thought, emotion and physical activity. However, neuroscientific evidence suggests that these are completely interlinked in the learning process. The traditional lecture-style lesson relegates students to a passive and sedentary role, precluding physical movement. In addition, the current trend of schools reducing recess hours, dropping physical education classes, or subjects that involve the whole body – theater, music, outdoor activity - further limits the scope for physical movement within the learning milieu. Neuroscientific evidence suggests that sedentarism impacts negatively on brain health, and not only physical well-being. Humans are designed to be on the move, to interact with their environment through movement: physical activity is a key contributing factor to healthy brain function. This mini review presents and analyzes evidence from diverse studies and meta-analyses showing the strong link between movement and cognition in primary and secondary school students. There is a growing body of neuroscientific evidence of the benefits that movement and physical activity have for cognition. In the research examined, the authors identify diverse types and degrees of physical activity and their impact on the brain. The neurological impact of movement on the brain can be understood at three levels: increased vascularization – oxygen and glucose to the brain – augmenting brain activity; the release of neurotransmitters and Brain Derived Neurotrophic Factor (BDNF) which favor neurogenesis, memory, attention and motivation; and the development of complex movement-related neural circuits and their interconnection with the executive brain functions. This article proposes a set of concrete applications for educators to bring movement into their classrooms and/or learning contexts, thus favoring cognition. Based on this evidence and given the current educational reality which generally approaches learning as an abstract activity divorced from our corporality, the authors argue for the need to incorporate physical activity and movement into the learning context.